2015 IEEE International Conference on Robotics and Automation (ICRA) 2015
DOI: 10.1109/icra.2015.7139764
|View full text |Cite
|
Sign up to set email alerts
|

RodBot: A rolling microrobot for micromanipulation

Abstract: We introduce the modelling and control of a rolling microrobot. The microrobot is capable of manipulating micro-objects through the use of a magnetic visual control system. This system consists of a rod-shaped microrobot, a magnetic actuation system and a visual control system. Motion of the rolling microrobot on a supporting surface is induced by a rotating magnetic field. As the robot is submerged in a liquid this motion creates a rising flow in front, a sinking flow behind, and a vortex above the robot, thu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 26 publications
0
27
0
Order By: Relevance
“…In this work, we present a MPC approach that deals with the constraints of the microrobotic system, the limitations of the actuation system and the disturbances due to the environment. The microrobot itself was introduced in [15] and analysed in [6]. This latter work showed that with a model-free controller, satisfactory tracking performance can be achieved (i.e.…”
Section: A Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…In this work, we present a MPC approach that deals with the constraints of the microrobotic system, the limitations of the actuation system and the disturbances due to the environment. The microrobot itself was introduced in [15] and analysed in [6]. This latter work showed that with a model-free controller, satisfactory tracking performance can be achieved (i.e.…”
Section: A Related Workmentioning
confidence: 99%
“…The second constraint in (6) gives restrictions on the states. This includes bounding the position of the RodBot as imposed by the borders of the camera image and the avoidance of obstacles (e.g.…”
Section: Constraint Definitionmentioning
confidence: 99%
See 1 more Smart Citation
“…A top camera observes the scene and image processing detects the position and orientation of the self-folding microrobot and provides feedback for the visual control system. Details of the visual control system is described in [11]. All the experiments are performed in a glass Petri dish placed in the middle of the workspace, filled with deionized water.…”
Section: B Experimental Setupmentioning
confidence: 99%
“…Kim et al [87] controlled a rolling spherical magnetic microrobot to follow a pre-defined spiral path. Pieters et al [88] controlled a rolling rod-shaped microrobot to follow a virtual target on a reference path, which is inspired by the trajectory following the control laws of unicycles. The controllers are similar to Controller I in Figure 6.…”
Section: Closed-loop Controlmentioning
confidence: 99%